If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -7 = 6x + 2 + -1(x + 12) Reorder the terms: -7 + 4x = 6x + 2 + -1(x + 12) Reorder the terms: -7 + 4x = 6x + 2 + -1(12 + x) -7 + 4x = 6x + 2 + (12 * -1 + x * -1) -7 + 4x = 6x + 2 + (-12 + -1x) Reorder the terms: -7 + 4x = 2 + -12 + 6x + -1x Combine like terms: 2 + -12 = -10 -7 + 4x = -10 + 6x + -1x Combine like terms: 6x + -1x = 5x -7 + 4x = -10 + 5x Solving -7 + 4x = -10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -7 + 4x + -5x = -10 + 5x + -5x Combine like terms: 4x + -5x = -1x -7 + -1x = -10 + 5x + -5x Combine like terms: 5x + -5x = 0 -7 + -1x = -10 + 0 -7 + -1x = -10 Add '7' to each side of the equation. -7 + 7 + -1x = -10 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = -10 + 7 -1x = -10 + 7 Combine like terms: -10 + 7 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| -k/5=18/10 | | 4(x-2)+4(x+1)=15-2x | | 7n+12=6-x | | 2x+2(2x-9)=360 | | 4(1.18)x+1=10 | | 4(5x-2)-20=15x-3 | | 3x=(5x+36) | | 3(1.07)x+1=12 | | (25x+4x+4)-(25x+5)=8x+16 | | w/10=49/40 | | 4(1.19)x+2=13 | | -6u^2-17u-5=0 | | X^2-26x-15=0 | | 3x+7x=18 | | (64x+6x+2)-(64x+3)=-9+15 | | -4(-x+7)+4=-(-5x-2)-1 | | (8-9i)/4i | | 5(c-4)+1c=70 | | -4X-56=-10+82 | | 3+x-x-1=(2-1) | | 64p^8q+24p^7q^3+40p^4q^2=0 | | 38+(7x+1)=(10x+9) | | 7=-8x-10 | | -32=3x+2(x+4) | | -18=-5(x-2)+7(x-6) | | -32 =3x+2(x+4) | | x/4-x/5-x/3=16/15 | | -21m-18=66 | | -32 = 3x + 2(x + 4) | | 3v^2-16v-12=0 | | 7(y-3)+6(y+1)=63 | | x-42=78+5x |